The Medical Gopher — A Microcomputer Based Physician Work Station - McDonald, Clement J. (1984)
We've developed a microcomputer medical work station intended to reduce the physician's “gopher” work of fetching, reviewing, organizing and writing that consumes his day. The system requires extensive physician interaction; so we have developed a fast and consistent menu-oriented user interface. It provides facilities for entering prescriptions, orders, problems and other medical record information and for generating flowsheets, executing reminder rules, providing ad hoc retrievals and reporting facts about drugs, tests and differential diagnoses. Each work station is connected to a central server (currently a VAX 117/80) in a network configuration, but carries all of its own programs, tables and medical records for a few hundred patients, locally. This system is tested but not yet tried. Questions remain about physician's acceptance and the true usefullness of such a work station.